Global incidence and profile of ameloblastoma: A systematic review and meta‐analysis. (25th January 2019) - Hendra, Faqi Nurdiansyah; Van Cann, Ellen M.; Helder, Marco N.; Ruslin, Muhammad; de Visscher, Jan G.; Forouzanfar, Tymour; de Vet, Henrica C. W.
Abstract: Objectives: To evaluate the global incidence of ameloblastoma and to provide a profile of ameloblastoma patients. Material and Methods: A systematic review and meta‐analysis was conducted. Searches were performed in PubMed, EMBASE, SCOPUS, and Web of Science for articles published from 1969 to 2018 for the global incidence and from 1995 to 2018 for the profile of ameloblastoma patients. Results: Seven studies on the incidence rate of ameloblastoma were included in the meta‐analysis. These studies only covered Europe, Africa, and Australia. The pooled incidence rate was 0.92 per million person‐years (95% CI: 0.57–1.49), with significant heterogeneity between studies. Forty‐two articles provided profile data of 6, 446 ameloblastoma patients. Mean age was 34 years and the peak age incidence in the third decade of life. In Europe and North America, ameloblastoma mostly occurred at an older age when compared to Africa and South America. A slight male preference (53%) was found, and the mandible appeared to be the preferred site. The most common type of ameloblastoma was multicystic. The histopathologic patterns were mostly follicular and plexiform. Conclusions: This is the first study assessing the global incidence of ameloblastoma. The pooled incidence rate was determined to be 0.92 per million person‐years.